The Effectiveness of Training to Improve Innovation in Banana Product Presentation on Human Resource Development by the Tourism, Youth and Sports Office - Fatmala, Kiki; Fahrudin, Fahrudin (Journal of Educational Management Research, 2025)
Human Resource Development (HRD) is an effort to improve human capabilities in order to increase company productivity. This research aims to analyze the Effectiveness of Training for Innovation Improvement in Banana Product Presentation on Human Resource Development by the Department of Tourism, Youth, and Sports. In this study, it is found that the independent variable (innovation improvement training) has a positive and significant effect on human resource development. This is proven by the results of the t-test, where the calculated t-value is 13.498, while the critical t-value is 2.014. Thus, it can be concluded that t-calculated > t-table, and the significance level is below 0.000 < 0.05, which means the alternative hypothesis (Ha) is accepted. Therefore, it can be concluded that partially, innovation improvement training has a positive and significant effect on human resource development in Rajekwesi Village. This means that if the village community frequently receives training, human resource development will improve. Conversely, the less training the community receives, the more difficult it will be to develop their human resources. This research also contributes to education by emphasizing the importance of practical, skill-based training as part of non-formal education. The findings highlight that targeted innovation training can enhance critical thinking, creativity, and entrepreneurial capacity key competencies in 21st-century learning.